2022
DOI: 10.3389/fbioe.2022.952194
|View full text |Cite
|
Sign up to set email alerts
|

A Superstable Homogeneous Lipiodol-Nanoformulation to Overcome the Dilemma of Interventional Embolization Chemotherapy

Abstract: Recent studies reported over 900,000 new HCC global cases by 2020, and by 2025, over one million people are expected to suffer with HCC every year (Siegel et al., 2022). For many years, surgical resection and liver transplantation have proved as primary methods for curative HCC treatment. However, liver decompensation after hepatectomy is a great concern for surgeons. Small-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Currently developed SHIFT ICG and SHIFT nanoICG have been applied in clinical trials of advanced HCC in many hospitals, obtaining satisfactory results through fluorescence-guided surgical navigation and embolization therapy. It is worth mentioning that the SHIFT technique could perfectly solve a clinical problem of difficult dispersion of strongly hydrophilic chemotherapeutic drug ( e.g., doxorubicin hydrochloride) in lipiodol for chemoembolization, showing long-lasting stability, sustaining drug release; it exhibits expected embolotherapeutic result for patients with advanced HCC. SHIFT technique provides a promising tool to solve clinical challenges of diagnostic and therapeutic procedures, offering hope to advanced patients in despair.…”
Section: Discussionmentioning
confidence: 99%
“…Currently developed SHIFT ICG and SHIFT nanoICG have been applied in clinical trials of advanced HCC in many hospitals, obtaining satisfactory results through fluorescence-guided surgical navigation and embolization therapy. It is worth mentioning that the SHIFT technique could perfectly solve a clinical problem of difficult dispersion of strongly hydrophilic chemotherapeutic drug ( e.g., doxorubicin hydrochloride) in lipiodol for chemoembolization, showing long-lasting stability, sustaining drug release; it exhibits expected embolotherapeutic result for patients with advanced HCC. SHIFT technique provides a promising tool to solve clinical challenges of diagnostic and therapeutic procedures, offering hope to advanced patients in despair.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional manual and three-way tube mixing methods for preparing iodized oil and drug emulsions are limited by the relatively low drugloading capacity and poor physical stability of the hydrophobic iodized oil and hydrophilic drug formulations. As a result, the drugs are quickly released into circulation, leading to poor therapeutic effects and severe adverse events [7,8]. The alternative method of drug-loaded microsphere embolization is costly and less effective due to microsphere size limitations [9].…”
mentioning
confidence: 99%
“…A phase 2 clinical trial has shown that treatment with nab-paclitaxel and gemcitabine-cisplatin (GC) had longer PFS and OS than GC alone (Shroff et al, 2019). The mechanisms underlying the antitumor effects of nab-paclitaxel include the promotion of tumor-associated antigen release, increased infiltration of tumor-infiltrating lymphocytes, and enhanced tumor cell permeability to granzyme (Weiss et al, 2017;Martin et al, 2020;Peng et al, 2022). Based on these encouraging results, combination therapy consisting of sintilimab, lenvatinib, and chemotherapy might be an optimal choice for cHCC-CCA.…”
mentioning
confidence: 99%